Fatigue crack growth analysis of different adhesive systems: Effects of mode mixity and load level. Issue 2 (15th November 2019) - Rocha, Ana V.M.; Akhavan‐Safar, Alireza; Carbas, Ricardo; Marques, Eduardo A.S.; Goyal, Rakesh; El‐zein, Mohamad; da Silva, Lucas F.M.
Abstract: The aim of this paper is to investigate the fatigue fracture behavior of three different adhesive systems (epoxy‐based, acrylic, and a rubber‐like adhesive). To achieve this, double cantilever beam specimens were manufactured with different adhesives and tested under several mode mixities and different load levels. Fatigue crack growth rate was evaluated through a Paris law equation. For postprocessing, the compliance‐based beam method was used. Results showed that the variation of the threshold energy with load level is more pronounced for the epoxy‐based adhesive. The crack propagation life is higher for the acrylic adhesive. Although, for pure mode I conditions, the normalized threshold of the rubber‐like adhesive is lower, for pure mode II, it was higher than the epoxy‐based adhesive. Due to the normalization by the static fracture energy, the slope of the Paris law was approximately constant for all the adhesive systems.